Anteromedial type of diaphragmatic defect is not a variation of Morgagni hernia [ANTEROMEDIYAL YERLESIMLI DIYAFRAGMA DEFEKTI MORGAGNI HERNISININ BIR TIPI DEGILDIR] - (:unkn) unknown (My University, 1996)
As presenting an uncommon anterior diaphragmatic defect in our two cases, we aim to emphasize its difference from Morgagni type parasternal diaphragmatic defect. One of the cases, 11-month old, had recurrent pneumonia, while the other one, 2-day old, presented with respiratory distress and cyanosis. In both cases preoperative radiologic examinations including upper gastrointestinal studies and computerize tomography revealed the presence of a large anterior defect and herniation of gastrointestinal organs into the mediastinum anterior to the heart. During the operations, a large ventral semilunar defects of the diaphragm were noted extending dorsally almost to the level of vena caval opening and anterolaterally to the rib cage of either side. Embryologic origin of these 5 to 6 cm defects were in the part of the diaphragm which corresponds to septum transversum in utero. There is uncertainty in the literature, how to name this uncommon type of congenital diaphragmatic hernia and usually this type of defect has been included in Morgagni hernia series. The hernia type we described here is neither anatomically nor clinically representative of Morgagni hernia. In reference to its' embryological origin this type of defect of diaphragm should be called as 'septum transversum hernia'.
Keywords: Diaphragm abnormalities; Hernia diaphragmatic